Legal implications of compulsory rainwater harvesting in Malaysia - Ab Rahman, Suhaimi; Othman, Mohd Shahwahid; Md Khalid, Rasyikah; Mohd Shahwahid, Farah (WFL Publisher, 2013)
Rainwater harvesting refers to a process that capture rainfall and use it for non-portable use like flushing and general washing. Although it has been promoted in Malaysia since 1999, the implementation of rainwater harvesting as an alternative supply of water is still very limited due to the current low rate of water supply. In 2006, the government proposed that rainwater harvesting wii be made compulsory to new large buildings as a measure to cope with drought and other impact of climate change. When the new law is passed, it may have some implications on the existing legal provisions. Compulsory rainwater harvesting requires amendment of certain laws since it attracts some planning, environmental and health issues. For instance, as design and requirement of a building are legislated under the Uniform Building By-laws 1984, it will be the most affected legislation and has to be amended accordingly. This paper shall analyse any affected legal provisions once rainwater harvesting is made compulsory. The content analysis method is used in analysing those provisions. The findings will be useful to support the new law on rainwater harvesting in Malaysia.